Minimum Quality Standard Under Cournot Competition and Pollution - Luca Lambertini; Alessandro Tampieri (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We extend the analysis carried out by Valletti (2000) by considering an environmental externality in a vertically differentiated duopoly where firms compete à la Cournot with fixed costs of quality improvement. We show that, if the weight of the external effect is high enough, the resulting minimum quality standard is indeed binding.
Keywords: L13; L51; Q50; 330